A Case Report of Tooth Wear Associated with a Patient's Inappropriate Efforts to Reduce Oral Malodor Caused by Endodontic Lesion - Masahiro Yoneda; Hatsumi Uchida; Nao Suzuki; Mariko Mine; Tomoyuki Iwamoto; Yosuke Masuo; Toru Naito; Yuko Hatano; Takao Hirofuji (Hindawi Limited, 2009)
Here, we report a case of severe tooth wear associated with a patient's inappropriate efforts to reduce oral malodor. A 72-year-old male patient visited our breath clinic complaining of strong breath odor. Former dentists had performed periodontal treatments including scaling and root planing, but his oral malodor did not decrease. His own subsequent breath odor-reducing efforts included daily use of lemons and vinegar to reduce or mask the odor, eating and chewing hard foods to clean his teeth, and extensive tooth brushing with a hard-bristled toothbrush. Oral malodor was detected in our breath clinic by several tests, including an organoleptic test, portable sulphide monitor, and gas chromatography. Although patient's oral hygiene and periodontal condition were not poor on presentation, his teeth showed heavy wear and hypersensitiving with an unfitted restoration on tooth 16. Radiographic examination of the tooth did not reveal endodontic lesion, but when the metal crown was removed, severe pus discharge and strong malodor were observed. When this was treated, his breath odor was improved. After dental treatment and oral hygiene instruction, no further tooth wear was observed; he was not concerned about breath odor thereafter.